Vitamin D status, enterovirus infection, and type 1 diabetes in Italian children/adolescents. Issue 5 (17th April 2018) - Federico, Giovanni; Genoni, Angelo; Puggioni, Anna; Saba, Alessandro; Gallo, Daniela; Randazzo, Emioli; Salvatoni, Alessandro; Toniolo, Antonio
Abstract : At the time of the clinical onset of type 1 diabetes (T1D), we investigated 82 pediatric cases in parallel with 117 non‐diabetic controls matched by age, geographic area, and time of collection. The occurrence of an enteroviral infection was evaluated in peripheral blood using a sensitive method capable of detecting virtually all human enterovirus (EV) types. While non‐diabetic controls were consistently EV‐negative, 65% of T1D cases carried EVs in blood. The vitamin D status was assessed by measuring the concentration of 25‐hydroxyvitamin D [25(OH)D] in serum. Levels of 25(OH)D were interpreted as deficiency (≤50 nmol/L), insufficiency (52.5‐72.5 nmol/L), and sufficiency (75‐250 nmol/L). In T1D cases, the median serum concentration of 25(OH)D was 54.4 ± 27.3 nmol/L vs 74.1 ± 28.5 nmol/L in controls ( P  = .0001). Diabetic children/adolescents showed deficient levels of vitamin D 25(OH)D (ie, 72.5 nmol/L) in 48.8% cases vs 17.9% in non‐diabetic controls ( P  = .0001). Unexpectedly, the median vitamin D concentration was significantly reduced in virus‐positive vs virus‐negative diabetics (48.2 ± 22.5 vs 61.8 ± 31.2 nmol/L; P  = .015), with deficient levels in 58.5% vs 31.0%, respectively. Thus, at the time of clinical onset, EV‐positive cases had reduced vitamin D levels compared with EV‐negative cases. This could indicate either that the virus‐negative children/adolescents had been hit by a non‐infectious T1D‐triggering event, or that children/adolescents with proper levels of vitamin D had been able to rapidly clear the virus. Thus, it would be important to assess whether adequate vitamin D supplementation before or during the prediabetic phase of T1D may counteract the diabetogenic potential of infectious pathogens.